Access to Subsidized Health Care Affects HIV Pre-Exposure Prophylaxis (PrEP) Uptake Among Gay and Bisexual Men in Australia: Results of National Surveys 2013–2019. (1st April 2021) - MacGibbon, James; Lea, Toby; Ellard, Jeanne; Murphy, Dean; Kolstee, Johann; Power, Cherie; Crawford, David; Bear, Brandon; De Wit, John; Holt, Martin
Abstract : Background: We assessed willingness to use HIV pre-exposure prophylaxis (PrEP) and current PrEP use among gay and bisexual men (GBM) in Australia. Methods: National, online cross-sectional surveys of GBM were conducted in 2013, 2015, 2017, and 2019. Willingness to use PrEP was measured on a previously validated scale. Trends and associations with key measures were analyzed using multivariate logistic regression. Results: During 2013–2019, 4908 surveys were completed. Among HIV-negative and untested men not currently using PrEP, willingness to use PrEP increased from 23.0% in 2013 to 36.5% in 2017 ( P < 0.001) but then plateaued at 32% in 2019 ( P = 0.13). The proportion of current PrEP users increased significantly from 2.5% in 2015 to 38.5% in 2019 ( P < 0.001). In 2019, factors independently associated with being a current PrEP user (compared with non-PrEP users who were willing to use PrEP) included having subsidized health care (Medicare), knowing HIV-positive people, being recently diagnosed with an STI other than HIV, having higher numbers of recent male sexual partners, recent condomless sex with casual and regular partners, and frequent PrEP sorting. Conclusion: Willingness to use PrEP has plateaued as its use has rapidly increased among GBM in Australia. PrEP use is concentrated among more sexually active men with access to subsidized health care. Free or low cost access schemes may facilitate broader access among GBM who want or need PrEP but lack access to subsidized health care.